2022
DOI: 10.3389/fcell.2022.886721
|View full text |Cite
|
Sign up to set email alerts
|

Age Dependent Changes in Corneal Epithelial Cell Signaling

Abstract: The cornea is exposed daily to a number of mechanical stresses including shear stress from tear film and blinking. Over time, these stressors can lead to changes in the extracellular matrix that alter corneal stiffness, cell-substrate structures, and the integrity of cell-cell junctions. We hypothesized that changes in tissue stiffness of the cornea with age may alter calcium signaling between cells after injury, and the downstream effects of this signaling on cellular motility and wound healing. Nanoindentati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 52 publications
1
20
0
Order By: Relevance
“…Previous studies showed that 27-week-old B6 mice cornea wounds healed more slowly than 9-week-old B6 mice corneas over the first 24 hours. 121 Likewise, in humans, corneal epithelial wound healing is delayed in aged individuals compared with younger people, possibly owing to a decrease in the regenerative capacity of the corneal epithelial cells. 122 Another possible reason is that aging corneal epithelial cells may exhibit changes in their cellular response to injury or inflammation that can lead to prolonged inflammation and, consequently, delayed healing.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that 27-week-old B6 mice cornea wounds healed more slowly than 9-week-old B6 mice corneas over the first 24 hours. 121 Likewise, in humans, corneal epithelial wound healing is delayed in aged individuals compared with younger people, possibly owing to a decrease in the regenerative capacity of the corneal epithelial cells. 122 Another possible reason is that aging corneal epithelial cells may exhibit changes in their cellular response to injury or inflammation that can lead to prolonged inflammation and, consequently, delayed healing.…”
Section: Discussionmentioning
confidence: 99%
“…In the cornea, pannexin 1 is decreased in stromal nerves as demonstrated in a mouse model (Cui et al., 2016; Rhodes et al., 2021). When the corneal epithelium (surrogate Schwann cells of corneal nerves) is injured or infected, injured cells release ATP via pannexin 1, which initiates calcium signaling events in the cornea and the tear film (Cui et al., 2016; Rhodes et al., 2021; Segars et al., 2022; Yang et al., 2019). Future studies are required to elucidate the exact role of pannexin 1 in corneal neuropathic pain.…”
Section: Mechanisms Involved In the Pathophysiology Of Neuropathic Painmentioning
confidence: 99%
“…Furthermore, when mast cells are activated, they secrete tryptase and interleukin-17, which instigate the activation of the protease-activated receptor-2 pathway on nerves, which fosters neurogenic inflammation and subsequent pain (Aich et al, 2015;Duchesne et al, 2011;Kulka et al, 2008). IL-17A receptors have been expressed and produced by nociceptor neurons and play an integral role by altering the expression of TRPV4 channels required in pain perception (Segond von Banchet et al, 2013).…”
Section: Corneal Epithelial Immunomodulationmentioning
confidence: 99%
“…Tears lubricate the ocular surface, carrying secreted molecules from corneal epithelial cells [10]. Tears represent the whole physiological status of the body [11,12].…”
Section: Introductionmentioning
confidence: 99%